First isolation of bovine coronavirus with a three-amino-acid deletion in the N gene causing severe respiratory and digestive disease in calve - Li, Siyuan; Yuan, Xuesong; Mao, Li; Cai, Xuhang; Xu, Xingang; Li, Jizong; Li, Bin (Frontiers in Microbiology, 2024)
Bovine coronavirus (BCoV), a persistent threat to global cattle industry, has caused significant economic losses worldwide. In this study, we first isolated a viral strain, named BCoV NXWZ2310, from the intestinal content of a diseased calve with severe diarrhea. BCoV NXWZ2310 was identified by cytopathic effects observation, indirect immunofluorescence assay and electron microscopy. Genomic analysis showed that BCoV NXWZ2310 belonging to the GIIb genotype and has a three-amino-acid deletion in the serine-rich region of the N gene. Importantly, the BCoV NXWZ2310 strain exhibited strong pathogenicity, causing nasal discharge and watery diarrhea in calves for 8 and 10 days, respectively. Viral shedding was detected in nasal, throat and rectal swabs at levels reaching 10 6.228 copies/mL, 10 5.0 copies /mL and 10 6.692 copies/mL, respectively. Pathological examination showed that NXWZ2310 resulted in parenchymal lesions of the pulmonary lobe and significant intestinal lesions. Both the lungs and intestines displayed marked microscopic lesions with clear viral antigens present. BCoV NXWZ2310 strain with N-gene deletion mutations, caused severe respiratory and digestive disease in calves. Therefore, effective strategies are needed for the prevention and control of this isolate.